The Reliability and Validity of a Four-Minute Running Time-Trial in Assessing V˙O2max and Performance - McGawley, Kerry (Frontiers in Physiology, 2017)
Introduction: Traditional graded-exercise tests to volitional exhaustion (GXTs) are limited by the need to establish starting workloads, stage durations and step increments. Short-duration time-trials (TTs) may be easier to implement and more ecologically valid in terms of real-world athletic events. The purpose of the current study was to assess the reliability and validity of maximal oxygen uptake (VO2max) and performance measured during a traditional GXT (STEP) and a 4-min running time-trial (RunTT). Methods: Ten recreational runners (age: 32 ± 7 y; body mass: 69 ± 10 kg) completed five STEP tests with a verification phase (VER) and five self-paced RunTTs on a treadmill. The order of the STEP/VER and RunTT trials was alternated and counter-balanced. Performance was measured as time to exhaustion for STEP and VER and distance covered for RunTT. Results: The coefficient of variation for VO2max was similar between STEP, VER and RunTT (1.9 ± 1.0, 2.2 ± 1.1 and 1.8 ± 0.8%, respectively), but varied for performance between the three types of test (4.5 ± 1.9, 9.7 ± 3.5 and 1.8 ± 0.7% for STEP, VER and RunTT, respectively). Bland-Altman limits of agreement (bias ± 95%) showed VO2max to be 1.6 ± 3.6 mL/kg/min higher for STEP versus RunTT. Peak HR was also significantly higher during STEP compared with RunTT (P = 0.019). Conclusion: A 4-min running time-trial appears to provide more reliable performance data in comparison to an incremental test to exhaustion, but may underestimate VO2max.